Rethinking Brahms - Grimes, Nicole ca. 20./21. Jh; Phillips, Reuben ca. 20./21. Jh (Oxford University Press, 2022)
Drawing on the expertise of a wide range of musicologists, performer-scholars, and music theorists, 'Rethinking Brahms' provides new perspectives on Brahms's music, the contexts of his creativity, and the reception of his works
Also issued in print: 2022. - Includes bibliographical references and index
Keywords: Brahms, Johannes / 1833-1897 / Criticism and interpretation; Brahms, Johannes / 1833-1897 / Appreciation; Music / ukslc; Music / thema; Music / 19th century / History and criticism